EFFECT OF ACTIVE CHARCOAL BAMBOO GEL (ACTIVATED CHARCOAL BAMBUSEAE) TOWARD DENTAL DISCOLORISATION - FUAD HUSAIN AKBAR (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the study was to determine the effect of the activated charcoal gel on tooth discoloration. Methods: This study was experimental laboratories and used a Pre-post-test only control group design. This study was conducted at the Pharmacy Laboratory of the State Islamic University of Alauddin Makassar and the Oral Biology Laboratory, Faculty of Dentistry, Hasanuddin University. The total samples were 30 maxillary incisors. The test tool used was Shade Guide VITAPAN® Classical. Data analysis using Wilcoxon Test and Kruskal Test Wallis. Results: Based on the results of the Wilcoxsondan test, the Kruskal Wallis test showed changes in tooth color after the application of bamboo charcoal gel at concentrations of 7.5%, 15%, and 30% with p values ​​<0.05. Conclusion: There was a significant change in tooth color before and after the application of bamboo activated charcoal gel.